CALDER - Neutrinoless double-beta decay identification in TeO2 bolometers with kinetic inductance detectors. Issue 6 (May 2016) - Vignati, M; Bellini, F; Cardani, L; Casali, N; Castellano, M G; Colantoni, I; Coppolecchia, A; Cosmelli, C; Cruciani, A; D'Addabbo, A; Di Domizio, S; Martinez, M; et al.
Abstract: Next-generation experiments searching for neutrinoless double-beta decay must be sensitive to a Majorana neutrino mass as low as 10 meV. CUORE, an array of 988 TeO2 bolometers being commissioned at Laboratori Nazionali del Gran Sasso in Italy, features an expected sensitivity of 50-130 meV at 90% C.L, that can be improved by removing the background from α radioactivity. This is possible if, in coincidence with the heat release in a bolometer, the Cherenkov light emitted by the β signal is detected. The amount of light detected is so far limited to only 100 eV, requiring low-noise cryogenic light detectors. The CALDER project (Cryogenic wide-Area Light Detectors with Excellent Resolution) aims at developing a small prototype experiment consisting of TeO2 bolometers coupled to new light detectors based on kinetic inductance detectors. The present R&D is focused on the light detectors. We present the latest results and the perspectives of the project.